Laryngeal recurrence sites in patients previously treated with transoral laser microsurgery for squamous cell carcinoma - P. Horwich; M. H. Rigby; C. MacKay; J. Melong; B. Williams; M. Bullock; R. Hart; J. Trites; S. M. Taylor (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The laryngeal framework provides a natural barrier preventing tumour spread to extralaryngeal structures. Transoral laser microsurgery (TLM) for laryngeal squamous cell carcinoma (SCC) may violate these boundaries, altering the pathways of tumor spread for potential recurrences. Our project objective is to describe laryngeal SCC recurrence patterns and overall survival in patients requiring total laryngectomy (TL) after TLM. Methods Patients undergoing TLM for laryngeal SCC requiring salvage TL were identified from a prospective CO2 laser database containing all patients undergoing TLM for head and neck malignancies at the QEII Health Sciences Center in Halifax, Nova Scotia between March 2002 – May 2014. Surgical pathology reports were analyzed for tumor characteristics, extent of recurrence and invasion of local structures. Kaplan-Meier analyses were performed to evaluate overall survival, disease specific survival (DSS) and locoregional control. Results Fifteen patients were identified from the database as receiving salvage TL for recurrent disease after initial TLM resection for laryngeal SCC. Final pathology reports demonstrated that 67% (10/15) of patients had thyroid cartilage involvement while 53% (9/15) of patients had cricoid cartilage involvement on salvage TL pathology. 33% (5/15) of patients had perineural invasion and 27% (4/15) had lymphovascular invasion. Mean and median follow-up times were 36.7 months and 26.8 months respectively (range 3.9–112.6). The Kaplan-Meier estimate for overall survival at 36 months was 40% post TL with a standard error (SE) of 13.6%. DSS was 47% (SE 14.2%), and locoregional control was 55% (SE 14.5%) post TL. Conclusions Laryngeal recurrence sites following TLM seem to be consistent with historical data at known laryngeal sites of vulnerability. Treatment with TLM does not predispose patients to a lower rate of locoregional control and overall survival after total laryngectomy and salvage outcomes are consistent with literature values.